Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada PT Lisa Concrete Indonesia di Kecamatan Kubu - Pranata, I Komang Sumandika Adhy; Suwena, Kadek Rai (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
In conducting this research activity, the purpose of the researcher is to carry out the testing process: (1) the effect given by Product Quality on Customer Satisfaction at PT Lisa Concrete Indonesia in Kubu District, (2) the effect given by Service Quality on Customer Satisfaction at PT Lisa Concrete Indonesia in Kubu District, and (3) the effect given by Product Quality and Service Quality on Customer Satisfaction at PT Lisa Concrete Indonesia in Kubu District. This activity uses a type of quantitative research. The population used by the researcher is consumers who have made purchases at PT Lisa Concrete Indonesia in Kubu District, so the number of samples that support this research is as many as 50. The sample technique used is the Random Sampling technique. The analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this study indicate that: (1) product quality has a positive and significant effect on customer satisfaction at PT Lisa Concrete Indonesia in Kubu District, (2) service quality has a positive and significant effect on customer satisfaction at PT Lisa Concrete Indonesia in Kubu District, (3) product quality and service quality simultaneously affect customer satisfaction at PT Lisa Concrete Indonesia in Kubu District.